Mothers Medical-based Experience as the Most Sought-after Online Information by New Mothers During Pandemic COVID-19 - Syifa Syarifah Alamiyah; Heidy Arviani; Zainal Abidin Achmad (The Journal of Society and Media, 2021)
In the past, new mothers were able to consult with their mothers about parenting and health issues. When they are married, many of them live not at home with their mothers. When they need information about childcare and health problems, they switch to using online information sources (Facebook, Instagram, the Health page, and WhatsApp group). This study explores how new mothers in Surabaya use online platforms to search for helpful information related to health during pandemic COVID-19. This study used a qualitative virtual ethnographic method by collecting data through interviews, FGDs, and participating in several online media platforms, including Facebook group Room for Children; id.theAsianparent.com; Instagram account @ruangmom, @kenapaharusvaksin, @obesitas, and WhatsApp œKulwapp group. The results reveal that new mothers prefer to enroll in Facebook private groups and only women members with open identities. While on Instagram, they prefer to communicate through questions and answer forums. The Health page that is the primary reference is id.theAsianparent.com. Meanwhile, involvement in the Kulwapp WhatsApp group is for convenience and safety to discuss issues surrounding sexual organs. The shifting information-seeking of new mothers to online platforms because of more theoretical and medically-based health information and experiences need.